The PENGEMBANGAN KEGIATAN MUSYAWARAH MELALUI MODEL PROBLEM BASED LEARNING (PBL) DALAM PEMBELAJARAN ILMU FIKIH DI MA’HAD ‘ALY PONDOK PESANTREN LIRBOYO KEDIRI - Wahyunisfah, Izzah; Basiran (Jurnal Studi Pesantren, 2024)
The success of learning can be achieved with the existence of an appropriate learning model. The learning model becomes more important than the material it self. The purpose of this study determined the implementation of the deliberation in learning fiqh at Ma'had 'Aly Lirboyo Kediri, as well as to determine the supporting and inhibiting factors for the implementation of the deliberation in learning fiqh at Ma'had 'Aly Pondok Pesantren Lirboyo Kediri. This paper is the result of qualitative research using interviews, observation, documentation. Data analysis carried out using qualitative descriptive analysis techniques. The approach used phenomenological approach. The data analysis technique used descriptive qualitative analysis with a phenomenological approach. Based on the results of research and data analysis, obtained 2 (two) types of deliberation models in learning fiqh at Ma'had 'Aly Pondok Pesantren Lirboyo Kediri; namely: first, group deliberation; and second, joint deliberation. Keywords: Deliberation Method, Jurisprudence Learning